Real Estate Business and its Impact on Urban Growth: A Study on Jalma Union, Batiaghata Upazila, Khulna - Alam, Md Ashraful; Rahman, Md Mustafizur (Journal of Bangladesh Institute of Planners, 2015)
Real estate business is now treated one of the main sources of revenue earnings from the developing sub-urban areas of Bangladesh. There is a high possibility that money will be invested in the real estate sector. Definitely real estate business generates the multiplier effect of invested money by creating formal and informal employment opportunities for different income groups. The real estate business is flourishing day by day in the fringe areas of Khulna city. Transformation is a continuous process. Resources, ecosystem biophysical environment, and land use on the surface of the earth undergo changes over time. This study shows that the land use pattern is changing rapidly and land price is being increased at a high rate without considering proper future development. The agricultural land and water bodies are being converted without plan degrading the land quality and damaging the biodiversity of the area. This study tried to find out land use transformation in one of the fringe areas of Khulna city during 1999 to 2014. The study has provided some findings about the changes in the diversity of development. The results of the analysis showed that the residential land use increased gradually during the study period and the agricultural land use decreased over the period. The real estate business of Khulna city plays an important role in the expansion of the city, but it cannot be considered a positive growth of urban area. That is why land use planning with proper policy guidelines are needed to addressee the emerging problems associated with real estate business and land use transformation in the fringe areas of the city. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 85-92